Exploring the perceptions of faculty members and students on cloud computing adoption in higher educational institutions of Bangladesh - Rahman, Mohammad Masudur; Suhaimi, Mohd Adam; Abd Rahim, Noor Hayani (Institute of Electrical and Electronics Engineers Inc., 2020)
he purpose of this paper is to explore on the perceptions of faculty members and students of tertiary institutions of Bangladesh regarding adoption of cloud computing in teaching and learning. The qualitative study used purposive sampling technique for selecting the 10 faculty members and 10 students from four private universities and four public universities of the capital city of Bangladesh. The researchers conducted a semi-structured interview with the participants. The data were coded, categorised and analysed inductively for a qualitative thematic pattern. The findings revealed that the faculty members and students agreed that using cloud computing was completely beneficial for them. However, the participants also opined that for some of them, technophobia towards adopting an innovation, the complexity of using technology, pop-up advertisements and lack of institutional infrastructure and trained staff